2019
DOI: 10.5223/pghn.2019.22.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Benign Recurrent Intrahepatic Cholestasis Type 2 in Siblings with Novel ABCB11 Mutations

Abstract: Benign recurrent intrahepatic cholestasis (BRIC), a rare cause of cholestasis, is characterized by recurrent episodes of cholestasis without permanent liver damage. BRIC type 2 (BRIC2) is an autosomal recessive disorder caused by ABCB11 mutations. A 6-year-old girl had recurrent episodes of jaundice. At two months of age, jaundice and hepatosplenomegaly developed. Liver function tests showed cholestatic hepatitis. A liver biopsy revealed diffuse giant cell transformation, bile duct paucity, intracytoplasmic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The Bile Salt Export Pump (BSEP), a member of the adenosino-triphosphate (ATP)-Binding Cassette (ABC) transporter family, utilizes ATP to transport substrates, such as taurocholate and other BS [15][16][17]. Genetic variability is present, evidenced by various mutations in in aforementioned genes [15][16][17][18][19][20][21]. New mutations in ATP8B1, ABCB11, and SLC51A genes have recently been reported [13,[15][16][17][18][19][20].…”
Section: Genetic Aspects Of Bric and Progressive Familial Intrahepati...mentioning
confidence: 99%
“…The Bile Salt Export Pump (BSEP), a member of the adenosino-triphosphate (ATP)-Binding Cassette (ABC) transporter family, utilizes ATP to transport substrates, such as taurocholate and other BS [15][16][17]. Genetic variability is present, evidenced by various mutations in in aforementioned genes [15][16][17][18][19][20][21]. New mutations in ATP8B1, ABCB11, and SLC51A genes have recently been reported [13,[15][16][17][18][19][20].…”
Section: Genetic Aspects Of Bric and Progressive Familial Intrahepati...mentioning
confidence: 99%
“…Several case studies have shown that rifampicin therapy may lead to reduced symptoms, improved biochemical parameters, and shortened episodes in benign recurrent intrahepatic cholestasis (BRIC) patients. [7][8][9][10] Rifampicin was also reported to be effective in patients with mutations in the adenosine 50-triphosphate binding cassette subfamily B member 11 (ABCB11) gene and MRP2 gene. 11,12 Van Dijk found that rifampicin can normalize serum bilirubin levels in patients with PHSF induced by drugs (e.g., flucloxacillin, clavulanic acid, anabolic steroid, oestradiol, and total parenteral nutrition) or transient biliary obstruction in formerly healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…PFIC consists of an intrahepatic accumulation of free bile acids that produce severe and chronic liver damage since early ages and make liver transplantation necessary in most cases [18,19]. Several mutated genes have been associated to PFIC, including transporters atp8b1 [20][21][22], abcb11 [23,24], abcb4/mdr3 [25][26][27][28] or tjp2 [18].…”
mentioning
confidence: 99%